An approach to historiographical studies about the working class and the working movements in Costa Rica - Angulo Brenes, Sonia (2023)
This article does an approach of the historiographical studies about the working class and the labor movements of the first half of the 20th century, in Costa Rica. It is showed from six identified tendencies the main topics and research objects, results and starting point to understand no only the appearance of this social class at the end of the XIX Century, as well as its main transformations along the XX Century. The main conclusions allude to the importance to continue in the update of this kind of studies about the topic through the deepening of new theorical, methodological and investigative edges.